2021
DOI: 10.18203/2320-1770.ijrcog20213832
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterisation and management outcomes of COVID-19 infection in pregnancy in a Nigerian tertiary hospital

Abstract: Background: Literature on the antenatal and perinatal management and outcomes of COVID-19 infection in pregnancy in Nigeria and sub-Saharan Africa is gradually emerging but sparse. There is an urgent need to build up the knowledge base of COVID-19 infection in Nigerian pregnant women. The objective of the current study was to determine the clinical characteristics and management outcomes of COVID-19 infection in pregnancy at the Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, Nigeria.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…] In this study the most frequent COVID-19 symptoms reported were cough, fever, headache, nausea/vomiting, and fatigue, have been corroborated by other studies [13,14]. In addition, nearly 50% of the patients were asymptomatic in Nigerian tertiary hospital [15].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…] In this study the most frequent COVID-19 symptoms reported were cough, fever, headache, nausea/vomiting, and fatigue, have been corroborated by other studies [13,14]. In addition, nearly 50% of the patients were asymptomatic in Nigerian tertiary hospital [15].…”
Section: Discussionsupporting
confidence: 85%
“…However, from our study findings, COVID-19 infection in pregnancy was associated with adverse perinatal and maternal outcomes. Preterm delivery/birth, the most common maternal/perinatal complication of COVID-19 infection in pregnancy reported in our study, may be a secondary complication of respiratory disease or directly induced by the viral infection [15]. COVID-19 can cause prelabour rupture of fetal membranes in the third trimester, leading to preterm labour [16].…”
Section: Laboratorymentioning
confidence: 64%
See 1 more Smart Citation